Meningkatkan Hasil Belajar PAI Dengan Penerapkan Metode Demonstrasi dan Bermain Peran Pada Mata Materi Q.S At-Tiin di UPT SD Negeri 08 Binjai Tapan - Nidarwati, Nidarwati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to implement the demonstration method in teaching and analyze its effect on students’ learning outcomes. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. In Cycle II, improvements were made based on the reflections from Cycle I, such as more heterogeneous groupings of students and increased guidance in demonstration activities. The observation results showed that while there was improvement in material mastery, some students remained passive in the learning process. Therefore, this study suggests improvements in supervision and student grouping to enhance the effectiveness of the demonstration method in teaching.